COMPLEMENT CLAUSES IN ABBOT ELEMENTARY MOVIE SERIES - Rahilla Fanny; Hendrokumoro Hendrokumoro (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2023)
This study aims to examine the English complement clauses in the Abbot Elementary film series. This studyusedaqualitative method with a descriptive approach. This study also used techniques of observing and noting. This study includedtwopurposes, they are described the complementizers used and what are the functions of complement clauses foundintheAbbotElementary film series. From the results of the analysis, it was found that the complementizers used were that, to, and-ing. Thefunction of the complement clause that was present as an object and a complement. Functioning as an object is indicatedbyacomplement clause that can be passive as a subject, while functioning as a complement in the Abbot Elementary filmseries is generallyindicated by the use of to in the complement clause. It is hoped that this research will contribute to the literacy of the Indonesianpeople, especially regarding the use of English complement clauses, how to translate them and use them in daily.